Efeitos da administração de Limosilactobacillus fermentum sobre pressão arterial e capacidade antioxidante no eixo êntero renal na prole de ratas alimentadas com dieta hiperlipídica durante gestação e lactação - Nascimento, Luciana Caroline Paulino do (2022)
The consumption of a high-fat diet during pregnancy and lactation has been considered a risk factor for the development of arterial hypertension in the offspring's adult life. In turn, modulation of the intestinal microbiota has been associated with benefits in blood pressure control, thus pointing to the need to investigate the effects of strains with probiotic capacity on diet-induced hypertension. Therefore, the present work aimed to investigate the effects of administration of Limosilactobacillus fermentum (L. fermentum) on renal function, blood pressure and oxidative parameters of the gut-kidney axis in the offspring of rats exposed to a high-fat maternal diet. For this, pregnant rats were fed a control diet (CTL) or high fat diet (HFHC) during pregnancy and lactation. At 90 days, in the offspring of the CTL and HFHC groups, blood pressure was evaluated by tail plethysmography and urinary and biochemical variables. Furthermore, in intestinal and renal tissue we analyzed levels of malondialdehyde (MDA), enzymatic (superoxide dismutase activity, SOD; catalase, CAT; and glutathione-S-transferase, GST) and non-enzymatic antioxidant defense (total thiols). In a second moment, following the same initial protocol, at 100 days, a group of HFHC rats was supplemented with a mix of L. fermentum (HFHC+Lf group) until 130 days. Therefore, the same analyzes of the first stage of the work were performed in the CTL, HFHC and HFHC+Lf groups. Our data indicate that the offspring of males and females of mothers fed the HFHC diet presented increased BP when compared to their respective CTL group. Male pups from HFHC dams showed reduced GST activity (30%, p<0.05) and colonic thiol content (28%, p<0.05), reduced SOD activity in the renal cortex (73%, p<0.05) and decreased urinary creatinine excretion (69%, p<0.001) when compared to the CTL group. Regarding female offspring, CAT activity and thiol content were reduced in the colon when compared to the CTL group (52% reduction, p<0.05 and 37%, p<0.05, respectively). Although lipid peroxidation increased in the renal cortex of female HFHC offspring (300%, p<0.05), CAT and SOD activities increased when compared to male offspring. At 130 days, the administration of L. fermentum strains reduced systolic, diastolic and mean blood pressure in male offspring. In the same group, we also observed an increase in SOD activity (24%, p<0.05) in the colon, while an increase in SOD (31%, p=0.05) and CAT (97%, p<0.05) in renal tissue with restoration of renal function compared to the HFHC group. It is concluded that the HFHC diet during pregnancy and lactation induces sex-specific oxidative stress along the gut-kidney axis in the offspring, which can induce renal dysfunction and arterial hypertension later on. However, the administration of L. fermentum promoted improvement in blood pressure levels, antioxidant capacity in the intestine-kidney axis and improvement in renal function in offspring in male rats.